Modificação química de taninos de Acacia mearnsii para obtenção de floculante livre de formaldeído - Machado, Grazielle Dias (2019)
The development of non-pollutant coagulants/flocculants aiming to replace conventional ones, usually toxic, has been extensively studied. A possibility is the obtainment of flocculants from tannins, compounds present in many plants. However, in order to use tannins as flocculants, their cationization is necessary, which is normally accomplished by Mannich reaction that requires formaldehyde addition, a toxic compound. Thus, the objective of this work was to synthesize a flocculant from tannins without using formaldehyde and optimize this synthesis through a Central Composite Rotational Design (CCRD). The optimized synthesis parameters were ammonium hydroxide to tannin extract ratio, in the range of 1:1 to 5:1, and reaction time, in the range of 1 to 4h. Evaluation of synthesized samples flocculant potential was accomplished by jar tests experiments, in which color and turbidity removal from a synthetic effluent based on humic acid 0,01% were evaluated, and the obtained results were compared to results obtained by a commercial flocculant derived from tannins, Tanfloc®. Synthesized flocculants were submitted to total solids determination, elemental, FT-IR and zeta potential analysis. Optimization results showed that reagents ratio has no linear influence on flocculant synthesis, while time linear effect and reagents proportion quadratic effect have significant influence on flocculant production. The flocculant synthesis methodology proposed on this study, alternative to Mannich reaction, showed excellent results regarding turbidity and color removal, since 100% of turbidity removal and 89.9% of color removal were achieved in optimized reaction conditions. This novel tannin based flocculant synthesis methodology is a promising technology to replace conventional coagulants/ flocculants, once it is environmentally friendly.